Generation and Analysis of Striated Muscle Selective LINC Complex Protein Mutant Mice - Stroud, Matthew J. (Methods Mol Biol, 2018)
The linker of nucleoskeleton and cytoskeleton (LINC) complex mediates intracellular cross talk between the nucleus and the cytoplasm. In striated muscle, the LINC complex provides structural support to the myocyte nucleus and plays an essential role in regulating gene expression and mechanotransduction. A wide range of cardiac and skeletal myopathies have been linked to mutations in LINC complex proteins. Studies utilizing tissue-specific knockout and mutant mouse models have revealed important insights into the roles of the LINC complex in striated muscle. In this chapter, we describe several feasible approaches for generating striated muscle-specific gene knockout and mutant mouse models to study LINC complex protein function in cardiac and skeletal muscle. The experimental procedures used for phenotyping and analysis of LINC complex knockout mice are also described.